Numerical and experimental study of a lens-lens beam generator solar concentrator. - Tawfik, Mohamed Mostafa Hassan (Cranfield University, 2018)
The increased risk of climate change, besides the rapid depletion of non-renewable sources, motivated researchers to replace non-renewable energy sources with renewable ones. Solar energy can be considered as the “mother” of all renewable energy sources. The research trend in concentrated solar power systems tends to study optimising the utilisation of such power source. However, most researches deal with building new facilities that uses solar thermal power efficiently. Although it is important to improve innovative designs for our energy future, parallel thinking in currently existing facilities is necessary. The aim of this work is to lower the Carbon footprint of currently existing conventional power systems that uses fossil fuels through hybridisation with solar energy efficiently. This would encourage countries, especially developing ones, to move forward to solar technologies. Therefore, an overview of different concentrated solar power (CSP) technologies is carried out. Among different CSP technologies, a two-stage lens system was used to generate a powerful and controllable concentrated solar beam, namely Lens-Lens Beam Generator (LLBG), is found to allow achieving the aim with minimum modifications requirements. The LLBG provides a unique flexibility in selecting the receiver location. This facilitates implementing solar energy in fossil-fuel systems which are currently in service and affording reduced land usage. However, it was built on a small scale with a restricted concentration ratio (CR) of 6.25 to avoid overheating its rear lens, using two bi-convex lenses. As a relatively high efficiency of 82.65% was reported at this low CR, it has the potential to achieve high CR values and higher thermal efficiency using a dual-axis tracking system. Building large aperture refractive-based solar concentrating systems tends to employ Fresnel lens geometry due to their cost and design advantages. Then, an evaluation of implementing Fresnel lenses in building such LLBG system became as the gap of knowledge for the current research. covering this gap required investigating the front and rear lenses geometries and materials. However, because of the UK location within a relatively low-DNI region with an average annual direct normal irradiation (DNI) of 400-1000 kWh/m², building a solar simulator for thermal testing arose as a critical need to achieve the required objectives within the limited research time-scale. Therefore, it became as one of the main research objectives of the present work. To fulfil this, different light sources have been reviewed and two of them are selected to be further studied. These selected light sources were metal halide and tungsten halogen. Metal halide lamps showed better match with solar spectrum over full spectral bandwidth compared to tungsten halogen light source. Despite that, utilising dimmable tungsten halogen lamp is more recommended for thermal testing, use as it provides controllable good output spectrum over the IR spectral zone. For the front lens design, manufacturing and cost studies carried out within the present work indicated that using plastic Fresnel lenses is the most cost-effective option for large-scale aperture refractive systems. Based on optical study performed, PMMA has been selected as the best material due to its higher ideal optical efficiency, compared to polycarbonate. For the rear lens geometry, thermal study indicated that positive meniscus geometry can withstand higher CRs, compared to both plano- and bi-convex geometries. Combination of thermal and optical studies showed that SiO₂ represents the optimum material for the rear lens, allowing highest CRs with maximum transmittance. Two Fresnel-based LLBG systems are designed and built to experimentally asses their performance. These systems were: prototype- and full-size systems, with results showing average field efficiencies of 17.30% and 17.65%, respectively, within 0.5m from the control mirror. By suppressing the influence of optical efficiencies due to different components used, a thermal conversion efficiency of 29.5% was obtained for both systems. These values showed that building a unit aperture area of an LLBG system can save up to 25.76 kg/year and 29.37m³/year of petroleum and natural gas, respectively. This can lead to annual CO₂ footprint reduction by 26.95 and 23.84 kgCO₂ for power generation systems that use combined cycles fuelled by petroleum and natural gas, respectively. Further optical investigation of Fresnel-based LLBG system to study the effects of different parameters on its performance. Although this investigation showed that IR spectrum deviates less than VIS and UV spectra, it also indicated that using Fresnel geometry for the front lens causes increases in the generated beam deviation angle. This reduces the system efficiency dramatically and its ability to carry the beam efficiently over long distances.
Keywords: COMSOL; ANSYS; sun; simulator; tracking; Fresnel